ITERATIVE MULTI-DRAFT MODELIN EXPOSITORY PROBLEM-SOLUTION COMPOSITION - Arfan Fahmi (Institut Teknologi Sepuluh Nopember, 2016)
University writing teachers in EFL writing programs are likely familiar with multi-draft composing. The researcher argues that multi-draft composing as it is currently used within second language writing programs can be overwhelming for EFL student. In this study, He introduces the iterative multi-draft model, a revised and more manageable version of the traditional multi-draft model, in EFL context. In a traditional multi-draft model, students generally complete a composition as part of a stand-alone, fixed-form writing unit and then move on to an entirely new and often unrelated genre. The students in this model learn a writing process and practice it in three unique and apparently unrelated compositions. Students in the iterative model learn a process and repeat it three times in compositions that clearly build on one another. He applies this model on EAP students to help master essential writing skills in expository composition. A study of 108 compositions written by 36 students in three meetingswithin two weeks in EAP course at Institut Teknologi Sepuluh Nopember ITS Indonesia rated by 2 raters demonstrates that the new model can be effective in improving students’ composition. The iterative model through a series of repeated measure univariate ANOVA produces a statistical effect on writing scores in three writing sub skills (content, F(5.34) at Sig 0.01, organization, F(15. 59) at Sig 0.00, grammar, F(16.91) at Sig 0.00, and overall F(20.31) at Sig 0.00). Additionally, the students’ perceptions of the model on 5 Likert-scale questionnaire further indicate that they have positive perspectives on their experience in applying this model (Mean = 4.42). This result supports the need for EFL writing instructors to continue to develop materials that teach the skills of process writing, genre recognition, and reader awareness. It also suggests to the prospective writer to read and understand at least three models before starting to write.